PERLINDUNGAN HUKUM MEREK SAH TERHADAP TINDAKAN PEMBONCENGAN REPUTASI (PASSING OFF) - Muhammad Faisal Aditya; Yudho Taruno Muryanto (Jurnal Privat Law, 2024)
AbstractThis article examines the form of legal protection for registered trademark rights holders against the existence of a passing off action along with what legal remedies can be taken by the aggrieved parties for the existence of this passing off act. So that through mechanisms both in litigation and non-litigation, it is hoped that it can provide justice for the aggrieved parties. This research is a normative-juridical research which is prescriptive in nature. Types of secondary data include primary, secondary and tertiary legal materials. The data collection technique used is through literature study, research instruments in the form of Undang-Undang No. 20 of 2016 concerning Trademarks and Geographical Indications. The results of this study indicate how the form of legal protection provided by the government for registered trademark rights owners against the act of passing off. The form of protection provided is in the form of granting exclusive rights to use a registered mark in the trade in goods / services, as a "differentiator" from the product against its competitors. In addition, it is explained in relation to the efforts that can be made by the aggrieved party if there is an action of passing off aimed at his brand. Efforts that can be made can be in the form of Application for Mark Cancellation in the Mark Official Gazette (during registration), the Litigation Path, and the Non-Litigation Path. AbstrakArtikel ini mengkaji terkait dengan bentuk perlindungan hukum bagi pemegang hak merek terdaftar terhadap adanya tindakan pemboncengan reputasi beserta upaya hukum apa yang dapat dilakukan oleh pihak-pihak yang dirugikan atas adanya tindakan pemboncengan reputasi tersebut. Sehingga melalui mekanisme baik secara litigasi maupun non-litigasi, diharap dapat memberi keadilan bagi pihak-pihak yang dirugikan. Penelitian ini merupakan penelitian normatif-yuridis yang bersifat preskriptif. Jenis data sekunder meliputi bahan hukum primer, sekunder dan tersier. Teknik pengumpulan data yang digunakan adalah melalui studi kepustakaan, instrumen penelitian berupa Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis. Hasil penelitian ini menunjukan tentang bagaimana bentuk perlindungan hukum yang diberikan oleh pemerintah bagi pemilik hak merek yang sudah terdaftar terhadap adanya tindakan passing off. Bentuk perlindungan yang diberikan tersebut adalah berupa pemberian hak eksklusif untuk menggunakan merek yang didaftarkan ke dalam perdagangan barang/jasa, sebagai “pembeda” daripada produk tersebut terhadap para pesaingnya. Selain itu dijelaskan terkait dengan upaya yang dapat dilakukan oleh pihak yang dirugikan apabila terdapat tindakan passing off yang ditujukan kepada mereknya. Upaya yang dapat dilakukan dapat berupa Permohonan Pembatalan Merek pada Berita Resmi Merek (saat pendaftaran), Jalur Litigasi, dan Jalur Non-Litigasi.